PENGARUH KEPRIBADIAN, DISIPLIN DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI SMESCO INDONESIA JAKARTA - Pitaloka, Fajar; Aprilia (Jurnal Gici Jurnal Keuangan dan Bisnis, 2023)
The development of the era of SMEs in Indonesia is increasing, in addition to getting benefits also to create new jobs. Therefore, there are various ways that business actors, especially the Micro, Small and Medium Enterprises (MSMEs) industry do to increase revenue turnover. The purpose of this study is to determine and analyze the influence of personality, discipline, and motivation on employee performance at Smesco Indonesia Jakarta This research method is quantitative with the type of research used is survey research. Sample selection is carried out by means of saturated sampling. The sample amounted to 102 respondents, using multiple linear regression analysis. The regression test results showed that 94.9% of performance factors could be explained by personality, discipline and motivation while the remaining 0.51% was explained by other factors not studied in this study. The results of the F test showed that simultaneously the variables personality, discipline and motivation simultaneously had a significant effect on performance. The results of the t test showed that personality and motivation variables had a positive and significant effect, while discipline variables did not have a positive and significant effect on employee performance at Smesco Indonesia Jakarta.